Enteric appendicitis: An unusual complication of enteric fever - Sandal, Sapna; Verma, Sanjay; Malik, Muneer Abas (Indian Journal of Child Health, 2017)
We present an 11-year-old boy admitted with fever, loose stools, vomiting, diffuse abdominal pain, and hepatosplenomegaly. Ultrasound and contrast enhanced computerized tomography of the abdomen was suggestive of appendicular lump. Widal done on day 8 showed elevated TO (1:320) and TH titers (1:80); repeat Widal on day 15 was suggestive of increasing titers (TO-1:320, TH-1:160). The patient improved with conservative management with intravenous ceftriaxone and azithromycin. This case highlights that appendicitis could rarely present as a complication of enteric fever in children; which may not always need surgery. In such cases, early initiation of appropriate antibiotics for enteric fever is curative.